2010
DOI: 10.1007/s00268-009-0334-6
|View full text |Cite
|
Sign up to set email alerts
|

Standard Outpatient Re‐Evaluation for Patients Not Admitted to the Hospital After Emergency Department Evaluation for Acute Abdominal Pain

Abstract: BackgroundThe aim of the present study was to investigate the efficacy and safety of standard outpatient re-evaluation for patients who are not admitted to the hospital after emergency department surgical consultation for acute abdominal pain.MethodsAll patients seen at the emergency department between June 2005 and July 2006 for acute abdominal pain were included in a prospective study using a structured diagnosis and management flowchart. Patients not admitted to the hospital were given appointments for re-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 17 publications
0
38
0
4
Order By: Relevance
“…2 However, evaluation of outpatient follow-up of emergency surgical patients presenting to the ED has not been well reported in the literature. 5 Onur et al conducted a randomised controlled trial showing that patients presenting to the ED with acute non-specific abdominal pain who were discharged home and followed up daily displayed no significant differences in either complications or morbidity compared with those admitted to hospital for observation. 6 Outpatient follow-up was deemed a safe course of management for these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 However, evaluation of outpatient follow-up of emergency surgical patients presenting to the ED has not been well reported in the literature. 5 Onur et al conducted a randomised controlled trial showing that patients presenting to the ED with acute non-specific abdominal pain who were discharged home and followed up daily displayed no significant differences in either complications or morbidity compared with those admitted to hospital for observation. 6 Outpatient follow-up was deemed a safe course of management for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…5 They prospectively evaluated patients presenting to the ED with acute abdominal pain who were not admitted to hospital but were asked to reattend a consultant-led outpatient clinic after 24 hours for re-evaluation. Following this re-evaluation, 46% were discharged home after only one visit to the clinic while 17% of reattending patients had their management plan changed, with 4% requiring a laparotomy (where previously only outpatient follow-up had been arranged).…”
Section: Pidgeon Shariff Devine Menon a Report On An Acute In-hoursmentioning
confidence: 99%
“…Several studies though, have demonstrated that medical history and physical examination alone lead to misdiagnosis resulting in delayed or inadequate treatment [1,2,14]. Therefore most patients are referred for additional imaging [3,6,13]. However, only 50% of patients with clinical suspicion, who are referred for imaging, are ultimately diagnosed with acute appendicitis or diverticulitis [1].…”
Section: Introductionmentioning
confidence: 99%
“…Acute abdominal pain accounts for almost 10% of all emergency department visits [1][2][3]. Acute appendicitis and acute diverticulitis are frequently suspected serious causes for acute abdominal pain [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation